Geomorfologia e urbanização no Vale do Aço: as planícies e a cidade de Ipatinga - Minas Gerais - Sueli Gentil Vasconcelos (2002)
The lack of studies about Vale do Aço Region, associated to the originality of its urban organization, was the motif for a research project that resulted in this master degree thesis.The region constituted by three municipal areas that reached an advanced process of conurbation (lpatinga, Coronel Fabriciano and Timóteo), totalizing more than 300,000 inhabitants is of great importance to Minas Gerais' economy. This is due to the very strong secondary sector, which characterizes and aids the steel production sector, generating large amount of taxes for the state and the region.Though we recognize the entire Vale do Aço region deserves detailed research , this project focu sed mainly on lpatinga City, due to the lack of time and data access. lpatinga City began and evolved side by side with the steel industry, when the internai and externai economy was headed to the postwar industrial expansion, including Brazil and other third world countries. Since the industrial installations depended heavily on their proximity's to a source of raw material (transportation technologies had great limitation at that time), the small nucleus still in Coronel Fabriciano's territory was chosen to be one of the world's biggest industries headquarters in the steel industry sector. From that point, changes were brutal, especially in terms of urban expansion. The tiny community where only 300 people lived in the late 1950's has, less than forty years later, a population of over 205.000. The environmental impact was impressive. There are areas occupied within a high standard of accuracy among others where urban risks are a permanent reality. This urban "logic", associated to the geological and geomorphologic characteristics, were the holdings of this study. This region of the middle Doce River valley, situated in the confluence of Piracicaba and Doce Rivers, inside typical tropical hilly relief (mar de morros}, sculpted over the predominantly Granitic-Gnaissic basement, presents a geomorphologic peculiarity: exceptionally thick sequences of alluvial sediments associated to extensive floodplain morphology in the urban area. To reach such purpose, it was necessary to do a survey of the cartographic data as well as percussion drilling data. lnitia lly it was done by private companies ordered by lpatinga City Hall and USIMINAS, to evaluate the constructions' substratum through a geotechnical point of view. Then these results were reinterpreted with support on geomorphologic approach. This procedure enabled us to work with a free prospect of the subsoil whose costs would be impossible to figure out.The topographic map, with 1:10.000 scale (lpatinga's Municipality), permitted a detailed study of the local morphology (and, when necessary, a study of the regional morphology) and served as a source for some geomorphologic profiles crossing distinct areas of lpatinga City, which were analyzed with precision. The percussion drilling data constituted the support for the study of subtratum's characteristics, interesting the basement's rocks as well as the alluvial sediments. From this analysis, it was possible to identify unstable areas submitted to erosion and floods. Even though it is known that riverbank occupation is one of the big local urban problems, no priority was given to its research. This work, therefore, focused basically on the problems that affect the extensive floodplains. Resulting from this approach, was drawn a map representing the areas affected by the recent floods, that occurred during 1999 and 2000 summers. As a result of the morphologic and geologic analysis it was possible to: build a map of the changes on Piracicaba River's channel, under natural conditions, through the Pleistocene Period; study the internai floodplains separated by some rocky prominence, including the identification of the characteristics of their alluvial sediments and the limitations of urbanization they imply; realize a sedimentological characterization of the Fundamental Plain. In terms of the urban expansion process, it was possible to relate it to the local morphological conditions. This enables us to monitor the distinct urbanization stages in lpatinga City, since the establishment of USIMINAS and its boroughs strategically placed over the remaining terraces, suitable for living, going through persistent Real Estate speculation in the city and the occupation of the outskirts, farther away from the city where it is less appropriate for living and finally ending with the beginning of vertical growth of urban building process in the 1990's that persists nowadays.